Protection circuit design of wireless power transfer systems - Sim, Jia Ee (Nanyang Technological University, 2022)
Wireless Power Transfer (WPT) system is the transmission of electrical power through space (theory of electromagnetic field) from a transmitter device, consisting of a power source to a receiver device, consisting of an electrical load unlike the traditional electrical power transfer through electrical cables. However, fault protection is need in any electrical system such as circuit breaker. In this Thesis, we study the protection method of using duty cycle of the inverter MOSFET to control the power supply of the WPT system